Analysis of the Employment of Nurses and Midwives: Data Analysis from Selected Hospitals in the Warmian-Masurian Voivodeship, Poland - Apolonia JASKOLSKA (Communications of International Proceedings, 2025)
The article analyzes the employment of nurses and midwives in selected hospitals in the Warmian-Masurian Voivodeship in 2022-2023. The reason for the selection is the shortage of nursing staff, which is a significant challenge for the healthcare system, affecting the quality of patient care and the working conditions of medical personnel. Despite reports indicating a shortage of nurses and midwives in Poland, there is a research gap in the literature, which indicates that the topic requires deeper research. The aim of the study was to determine the dynamics of changes in the employment of nurses and midwives and their impact on the functioning of facilities. For this purpose, a comparative analysis of employment in three hospitals in Poland was used. To sum up, the analysis showed a slight increase in the number of employed nurses and midwives, which still does not compensate for the growing demand for qualified medical staff. Further strategic action is needed at both local and national levels.
Keywords: Employment in hospitals; hiring; nurses and midwives; healthcare entities.